Pharmacotherapy of Alzheimer's disease - Gauthier, Serge; Cuello, A. C (Martin Dunitz, 1998)
The publication focuses on the treatment of Alzheimer ́s disease using new drugs. Intended for professional public.
Keywords: farmakoterapie; léčivé přípravky; Alzheimerova nemoc; Pharmaceutical Preparations; Alzheimer Disease; neurologie